Integrative taxonomy allows the identification of synonymous species and the erection of a new genus of Echiniscidae (Tardigrada, Heterotardigrada) - Vicente, Filipe; Fontoura, Paulo; Cesari, Michele; Rebecchi, Lorena; Guidetti, Roberto; Serrano, Artur; Bertolani, Roberto (Zootaxa, 2013)
The taxonomy of tardigrades is challenging as these animals demonstrate a limited number of useful morphological char-acters, therefore several species descriptions are supported by only minor differences. For example, Echiniscus oihonnae and Echiniscus multispinosus are separated exclusively by the absence or presence of dorsal spines at position Bd. Doubts were raised on the validity of these two species, which were often sampled together. Using an integrative approach, based on genetic and morphological investigations, we studied two new Portuguese populations, and compared these with ar-chived collections. We have determined that the two species must be considered synonymous with Echiniscus oihonnae the senior synonym. Our study showed generally low genetic distances of cox1 gene (with a maximum of 4.1%), with specimens displaying both morphologies sharing the same haplotype, and revealed character Bd to be variable. Addition-ally, a more detailed morphological and phylogenetic study based on the 18S gene uncovered a new evolutionary line within the Echiniscidae, which justified the erection of Diploechiniscus gen. nov. The new genus is in a sister group rela-tionship with Echiniscus and is, for the moment, composed of a single species.